Financing policy adopted by companies and their financial performance: a case study on the Malaysian groom big (2) companies / Sharifah Fadzlon Abdul Hamid, Suzana Sulaiman and Normah Omar - Abdul Hamid, Sharifah Fadzlon; Sulaiman, Suzana; Omar, Normah (Universiti Teknologi MARA Cawangan Selangor, 2017)
This paper intended to study the financing policy adopted by small and medium sized companies (SME). The finding was as a result from a consultancy programme conducted on five out of thirteen Groom Big (2) companies. These companies were identified and selected by the Malaysian Productivity Corporation (MPC), with the initiative to encourage, nurture and develop these SME entrepreneurs to become bigger entity and thus to enable them to compete domestically and globally. The companies comprised of food, pharmaceutical products, fixtures and parts for local car manufacturers as well as multi-service. The study focused more on the financial accounting statements of the companies, in particular the financing of these companies and its performance ratio. Additional information were collected during site and through focus group interviews. The analysis of the financial statements were conducted over three years and the results showed that the financing policy adopted by the Groom Big Companies varies and have different effects on the financial performance.